ABC transporters knockout in Aedes aegypti induces upregulation of paralogous genes, avoiding resistance development to Bacillus thuringiensis Cry toxins - Sabino Pacheco; Marcos Chiñas; Juan Ulises Gómez; Ángel Enrique Peláez-Aguilar; Nathaly Alexandre do Nascimento; Pablo Emiliano Cantón; Jorge Sánchez; Samira López-Molina; Isabel Gómez; Mario Soberón; Alejandra Bravo (PLoS ONE, 2025)
ABC transporters are membrane proteins that modulate the insecticidal activity of Bacillus thuringiensis Cry toxins by acting as receptors in the gut epithelium of insect larvae. However, their role as Cry receptors in dipteran species remains unknown. Here, we identified the ABC transporter orthologs in the Aedes aegypti genome corresponding to the Cry toxin receptors described in lepidopteran and coleopteran species. Analysis of their transcriptomic regulation in gut tissue, revealed the expression of ABCA2, ABCB1, and ABCC2. Using CRISPR-Cas9, we knocked out (KO) the expression of these three ABC transporter genes and performed in vivo binding assays and bioassays with four mosquitocidal Cry toxins (Cry4Aa, Cry4Ba, Cry11Aa, and Cry11Ba). Histopathological analysis showed a significant reduction of Cry toxins binding to the apical microvilli membrane of gut epithelium, depending on the ABC KO mutation. However, similar larvicidal activity was observed for Cry toxins between ABC KO and wild type strains. Transcriptomic analysis revealed specific upregulation of their corresponding ABC transporter paralogous, suggesting a compensatory mechanism that could mitigate the fitness cost of the ABC KO and potentially contribute to redundant receptor function of Cry toxins. These findings provide evidence that ABC transporters may act as physiological receptors for insecticidal Cry toxins in dipteran insects.